Covid-19 and the impact on young athletes - Fitzgerald, H. T.; Rubin, S. T.; Fitzgerald, D. A.; Rubin, B. K. (Paediatric Respiratory Reviews, 2021)
The Covid-19 pandemic has disrupted organised sport in the community as authorities cancelled, greatly modified or postponed sporting participation as part of a strategy to reduce transmission of the virus. This had a significant impact on young athletes and their families in relation to their psycho-social, physical and career progression considerations. The disruption is likely to continue for some years, considering the constraints of lockdowns, the need to overcome dysfunctional national logistics for delivery of medical care, fund and implement an efficacious vaccine programme locally, nationally and worldwide, develop sufficient herd immunity and create an environment of confidence in the safety of returning to sports for participants, coaches, umpires, administrators and observers. This article will consider the interim challenges regarding the physical and psychosocial importance of maintaining an active sporting programme for young athletes, reflect on safety measures for modifying sporting equipment and environmental protections to allow safest participation in training and competition and provide advice on protocols for a gradual return to sport for the young athlete after infection with Covid-19.